Exploring Language Politeness in Mandailing Onang-Onang Oral Traditions: A Pathway to Enriching Islamic Education - Rosmilan Pulungan; Hasanuddin WS; Novia Juita (Nazhruna: Jurnal Pendidikan Islam, 2025)
Politeness in language is essential for fostering respectful communication and social harmony, particularly within cultural and religious contexts, yet its role in Islamic education remains underexplored. This study examines how the Mandailing Onang-Onang oral tradition encapsulates linguistic politeness strategies that reflect Islamic values and explores its potential contribution to Islamic education. Employing a qualitative ethnographic approach, the research utilizes participant observation, in-depth interviews with cultural practitioners, and analysis of recorded Onang-Onang performances framed through Brown and Levinson's politeness theory. The findings reveal that Onang-Onang employs key politeness strategies, such as indirectness, honorifics, and metaphorical expressions, which align with Islamic ethical principles of morality (akhlaq) and etiquette (adab). Furthermore, the study underscores the role of Onang-Onang in reinforcing communal ties and transmitting religious teachings. Integrating Onang-Onang into Islamic educational frameworks can enrich moral instruction, preserve cultural heritage, and strengthen learners' understanding of Islamic values, demonstrating its relevance in contemporary pedagogical settings.